Exploring the research progression and evolutionary trends of gut microbiome and hypertension: a bibliometric analysis - Huang, Xinyu; Liu, Yingying; Jiang, Feng; Xin, Laiyun; Wang, Zhenyuan; Hua, Zhen; Wang, Cong; Zhang, Lei; Yu, Jie (Frontiers in Microbiology, 2025)
Hypertension is one of the most common cardiovascular diseases, with multiple underlying mechanisms. The gut microbiome, as one of the most important microbial communities in the human body, plays a significant role in the development of various diseases, including hypertension. While numerous studies have explored the relationship between gut microbiome and hypertension from different perspectives, there has been no bibliometric study in this field. Therefore, a bibliometric analysis is crucial for accurately assessing and summarizing the current research status. The analysis indicates that the number of publications in this field has steadily increased in recent years, with China and the United States leading in development. The journal Nutrients has the highest number of published papers, and Marques, Francine Z is a prominent figure with significant contributions and influence in this field. Co-occurrence and trend analysis suggest that the main research hotspots include the relationship between gut microbiome and hypertension, mechanisms by which gut microbiome promotes hypertension, and new therapeutic strategies targeting gut microbiome to improve hypertension. Future research trends may focus on expanding new metabolites or measurement techniques, building databases of human and animal gut microbiota and their metabolites, and developing new drugs targeting gut microbiota for hypertension. In summary, this study visually demonstrates the dynamic changes in research hotspots, revealing new patterns and focuses in the field, and aims to provide new insights for clinical work on hypertension.